The Indian Mutiny of 1857 and the Cape Colony (Historia, 2021)
The Indian Mutiny of 1857 was probably the most significant event in the history of British India during the 19th Century. For a brief time it was feared that the subcontinent might be lost to British rule. But this was not to be, and even as the Mutiny was being stamped out, British policy towards India reflected a determination to prevent another uprising. Symbolic of this was the replacement of East India Company rule by that of the Crown in 1858. The India Office was established and by 1866 was housed in a resplenent new building in King Charles Street, Whitehall. Yet, in spite of considerable alarums and excursions, no serious attempt has been made to see the Mutiny as the epicentre of an imperial earthquake whose tremors were felt in far-removed segments of the Empire. This article seeks to explore the influence of the Mutiny on the Cape Colony. The investigation will confirm that the events of 1857 in India affected the Cape Colony in a number of ways  already recognized by some historians, but it will elaborate on them and also bring to the fore a number of developments hitherto ignored.
Keywords: J Rutherford; British Empire; Cape of Good Hope; Indian mutiny; History; Sir. G. Grey; Historia; Cape Colony; Indian Mutiny